Intensification of a novel absorption-microalgae hybrid CO2 utilization process via fed-batch mode optimization. (March 2019) - Song, Chunfeng; Liu, Jie; Xie, Meilian; Qiu, Yiting; Chen, Guanyi; Qi, Yun; Kitamura, Yutaka
Graphical abstract: Highlights: Batch-feeding modes of NH4HCO3 for absorption-microalgae hybrid process were optimized. Influence of batch-feeding modes on NH3 escape was investigated. Carbon conversion efficiency of hybrid process was intensified via batch-feeding modes optimization. Value-added ingredients variation with batch-feeding modes was also evaluated. Abstract: Ammonia-absorption-microalgae hybrid CO2 capture process presented the potential advantages in cost-effective CO2 capture and bioconversion. However, cultivation mode still needs to be intensified to reduce the negative influence of NH3 escape and its inhibition on microalgae growth. In the current work, three batch feeding modes of ammonium (i.e. NH4 HCO3 ) for two Chlorella sp. (UTEX1602 and L38) were investigated. The experimental results indicated that initial NH4 HCO3 deficiency (mode A) was beneficial for microalgae growth compared to the cultivation modes of uniform feeding (mode B) and decreasing dosage (mode C). Chlorella L38 presented a higher growth rate than UTEX1602, and might be more suitable for absorption-microalgae hybrid CO2 capture system. In detail, carbon utilization efficiency could achieve up to 76.8% in the absorption-microalgae hybrid process, which was two to three times higher than the conventional microalgae CO2 fixation processes. NH3 escape rate in absorption-microalgae hybrid process could be reduced to 24.2%, which was 18.8% lower than the conventional ammonia CO2 absorption process. Moreover, nitrogen and carbon in NH4 HCO3 could be converted into biomass and value-added ingredients to realize resource recycling.